2001
DOI: 10.1351/pac200173101641
|View full text |Cite
|
Sign up to set email alerts
|

Critical evaluation of stability constants of phosphonic acids (IUPAC Technical Report)

Abstract: Republication or reproduction of this report or its storage and/or dissemination by electronic means isAbstract: Available experimental data on stability constants of proton and metal complexes for 10 phosphonic acids [methylphosphonic acid, 1-hydroxyethane-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
165
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 244 publications
(189 citation statements)
references
References 25 publications
12
165
0
1
Order By: Relevance
“…Etidronic acid is currently one of the most popular chelating agents and is widely used in various applications, such as in medicines, commercial washing agents, and inhibitors for corrosion protection. Etidronic acid is a tetraacid that features four acidic hydroxyl groups with the following acid dissociation constants, pKa [50,51] 1 and pKa 2 values as indicated above, it is expected that etidronic acid has the potential to behave as a suitable electrolyte for fabricating anodic porous alumina. We found that etidronic acid anodizing under appropriate electrochemical conditions provided highly ordered anodic porous alumina with a large-scale cell diameter, approximately 530-670 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Etidronic acid is currently one of the most popular chelating agents and is widely used in various applications, such as in medicines, commercial washing agents, and inhibitors for corrosion protection. Etidronic acid is a tetraacid that features four acidic hydroxyl groups with the following acid dissociation constants, pKa [50,51] 1 and pKa 2 values as indicated above, it is expected that etidronic acid has the potential to behave as a suitable electrolyte for fabricating anodic porous alumina. We found that etidronic acid anodizing under appropriate electrochemical conditions provided highly ordered anodic porous alumina with a large-scale cell diameter, approximately 530-670 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The complex structure proposed in the literature (see Figure 6) for the complex with only two nitrogen atoms and one phosphonate group chelated to Mn(II) forming a stable cyclic structure is highly improbable, as it would imply a q value too high to be compatible with the observed r 1 [31]. There is evidence that aminophosphonate ligands with two or more phosphonate groups have lower coordination tendencies than expected due to the mutual repulsion between adjacent binegative phosphonate groups [32,33]. This is reflected in the stability constants of the MnL 1 and MnL 2 , which are smaller than those of the corresponding carboxylate analogues EDTA and HDTA [31].…”
Section: Proton Relaxivitiesmentioning
confidence: 92%
“…It has been shown that saline solutions tend to promote calcite dissolution (salt effect), thus leading to an increased release of Ca 2+ . 64 65 while the solubility of phosphonate complexes with alkaline-earth metals increases in the order Ca < Ba < Sr < Mg. 45 Thus, in the presence of magnesium no precipitate will form and phosphonate molecules will adsorb (physisorption) onto calcite surfaces.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%